Denaturalizing Life-size Displays of Architecture: 1:1 Period Rooms by Andreas Angelidakis. Issue 1 (2nd January 2019) - Liefooghe, Maarten
Abstract: In 2015 Het Nieuwe Instituut in Rotterdam programmed the exhibition 1:1 Period Rooms by Andreas Angelidakis, an environment featuring six evocations of historical period rooms, gradually evicted from the Stedelijk Museum as it adopted the white cube convention. This article interprets the exhibition, its six period room-white cube permutations, and Andreas Angelidakis's multiple authorial identity as an architect–artist–curator by positioning them at the crossroads of three interlocking contemporary 1:1 exhibition practices. The show is first contextualized within a current trend of 1:1 exhibition structures in architecture exhibitions increasingly used to address tensions between image and construction in the representation of architecture itself. The second and third reference fields are the institution–critical interventions on the exhibition space in artistic and curatorial projects from the late 1960s onwards, and the more recent reconstructions of historical displays and re-exhibitions of significant exhibitions.